A Mendelian Randomization Study of the Effect of Type‐2 Diabetes and Glycemic Traits on Bone Mineral Density. (12th January 2017) - Ahmad, Omar S; Leong, Aaron; Miller, Julie Ann; Morris, John A; Forgetta, Vincenzo; Mujammami, Muhammad; Richards, J Brent
ABSTRACT: Type‐2 diabetes (T2D) is associated in observational studies with both higher bone mineral density (BMD) and higher fracture risk for given BMD. These relationships may however be confounded by factors such as body mass index (BMI). Here we used Mendelian randomization (MR) to obtain non‐confounded estimates of the effect of T2D and glycemic traits on BMD. We identified genetic variants strongly associated with T2D risk (34, 840 T2D cases and 114, 981 controls) and fasting glucose (133, 010 nondiabetic individuals), but not associated with BMI, and determined the effects of these variants on BMD (up to 83, 894 individuals). Using these variants as instrumental variables, we found that a genetically‐increased risk of T2D increased femoral neck BMD (+0.034 SD in BMD per unit increase in log‐odds of T2D [95% CI, 0.001 to 0.067; p = 0.044]). Genetically‐increased fasting glucose also increased femoral neck BMD (+0.13 SD in BMD per mmol/L increase in fasting glucose [95% CI, 0.01 to 0.25; p = 0.034]). Similar nonsignificant trends were observed for the effects of T2D and fasting glucose on lumbar spine BMD. Our results indicate that both genetically‐increased T2D risk and genetically‐increased fasting glucose have weak positive effects on BMD. © 2016 American Society for Bone and Mineral Research.